Making video tutorials to help St. Francis of Assisi Parish in practicing the Dolo-dolo motive Ordinarium - Maria Klara Amarilis Citra Sinta Dewi Tukan; Agustinus Beda Ama; Paskalis Romanus Langgu; Agustinus Renaldus Afoan Elu; Elvis Albertus Bin Toni (University of Merdeka Malang, 2022)
In regular masses, the ordinarium song consisting of Kyrie, Gloria, Sanctus, and Agnus Dei with Dolo-dolo motif is the most frequently sung. However, in reality, mistakes often happened when singing this ordinarium song, including inaccuracies in terms of accent and rhythm that do not characterize as the Dolo-dolo motif. This Community Service activity aims to help the parishioners of St. Fransiskus Assisi at BTN-Kupang City to sing the ordinarium song with the Dolo-dolo motif properly and correctly through producing tutorials. Making tutorials began with studying the ordinarium song with the Dolo-dolo motif by Matheus Weruin. Based on the results of the study, the team then made a video tutorial on how to sing the ordinarium song in a good and correct Dolo-dolo motif, starting from how to read the notation to reading the lyrics/poems. As meant to make it easier for people to learn the material provided. The most important matter emphasized in each tutorial is the accent and rhythm of the Dolo-dolo motif of each song. Based on the results from trials in small choir groups and evaluation with partners, using the video tutorial that has been made, the group was able to sing the ordinarium song with the Dolo-dolo motif properly and correctly for each type of sound or combined sound. The video was distributed to choir teams in the parish to be rehearsed and sung in celebration of the mass.